Influence of genetic and environmental factors on the immunogenicity of Hib vaccine in Gambian twins. - Lee, Y; Newport, M; Goetghebuer, T; Siegrist, C; Weiss, H; Pollard, A; Marchant, A (2006)
The differences in incidence rates of Haemophilus influenzae type b disease and the variation in Hib conjugate vaccine efficacy achieved among different ethnic groups suggest genetic influences on the immune response to Hib vaccine. The serum anti-PRP antibody concentration of 43 monozygotic (MZ) and 147 dizygotic (DZ) twin pairs in the Gambia was measured using a standardised Hib ELISA. Intrapair correlations for MZ and DZ twin pairs were compared and heritability in antibody responses to Hib conjugate vaccine was estimated to be 51% (95% CI: 32-66%), indicating a significant genetic contribution in the response. We conclude that genetic factors may be involved in the variation in immune response to Hib vaccine observed in different populations and may contribute to cases of vaccine failure.